Relationship between Bioethanol Production and Agricultural Commodity Prices: for the case of Thailand - Nathan, Thurai Murugan; Senadjki, Abdelhak; Chee, Keong Choong; Nor Asmat, Ismail (School of Social Sciences, 2015)
This paper examines the relationship between bio-ethanol production and agricultural commodity prices in Thailand. The main feedstocks for producing bioethanol in Thailand are sugarcane, cane molasses and cassava. Monthly data has been used from January 2006 to March 2014 to conduct this research. The existence of long-run relationships among the four variables i.e. bioethanol production, sugarcane farm gate price, cane molasses export price and cassava farm gate price detected through the Auto Regressive Distributive Lag (ARDL) framework. Then, the Granger Causality Test (Wald Test) used to investigate the short-run causal relationship among those variables. From the result found that when bioethanol production act as independent variable, long-run equilibrium exist between bioethanol production and sugarcane farm gate price, cane molasses export price and cassava farm gate price, respectively. Besides that, Granger causality exists among the variables as well. Sugarcane farm gate price and bioethanol production as well as cassava farm gate price and bioethanol production are found to be having unidirectional Granger causality effect. Meanwhile, bidirectional Granger causality effect is found between cane molasses export price and bioethanol production. The results of this study would contribute towards significant policy making in Thailand.